Penggunaan Mise-En-Scene pada Penyutradaraan Video Feature Berdaya, Berkarya, Bermakna bagi Disabilitas - Ridha Rizqiyanty Robina; Santi Susanti; Rinda Aunillah Sirait (Lembaga Pengembangan Kinerja Dosen, 2025)
The video feature Berdaya, Berkarya, Bermakna bagi Disabilitas aims to highlight the potential and creative works of children with disabilities at the Our Dream Indonesia Foundation through a mise-en-scène approach that enhances both visual and emotional narratives. This writing is motivated by the urgency of promoting the economic and social empowerment of persons with disabilities and the need to challenge prevailing stigmas through mass media. The 11-minute video feature integrates cinematography, set design, costume and makeup, and lighting to construct an engaging and informative storytelling experience. The objective of this study is to explain the production process of creating a visual work using mise-en-scène elements, which includes three key stages: pre-production (research, field observation, storyline development, storyboard creation, and technical preparation), production (filming using cinematographic techniques), and post-production (editing and visual refinement). The findings indicate that the comprehensive application of mise-en-scène successfully reinforces the message of inclusivity. For example, the use of cinematographic techniques contributes to the visual aesthetics; the set design of Toko Amis Budi shows the works of children with disabilities; the makeup and costume choices reflect the personalities of the featured subjects; and the lighting enhances the emotional tone of each scene. In conclusion, this work affirms that mise-en-scène not only enriches the visual appeal but also deepens the emotional impact, transforming facts into inspiring stories and raising public awareness of the importance of expressive spaces for individuals with disabilities. This video serves as an effective medium to advocate for equal rights and the recognition of the abilities of persons with disabilities.